Analysis Of The Influence Of The Tourism Sector On Pad Of The Tourism Sub-Sector In The District/City Of The Special Region Of Yogyakarta (2013-2021) - Sultan, Sultan; Fattah, Rakazeta Yusuf (AIBPM Publisher, 2024)
This research aims to analyze the influence of the number of tourist visits, the number of tourist attractions, and the number of non-star hotels on the Regional Original Income of the Tourism Sub Sector in the Districts/Cities of the Special Region of Yogyakarta Province in 2013-2021. This research is based on secondary data, namely the number of tourist visits, number of tourist attractions, and local revenue from the tourism sub-sector which is available in the Tourism Statistics of the Yogyakarta Special Region Tourism Office in 2013-2021 as well as the number of non-star hotels available in the Central Statistics Agency in 2013-2021. The analytical tool used is Panel Data Regression with the Random Effect Model (REM) approach. Based on the results of the analysis, it is known that the variables number of tourist visits and number of non-star hotels have a significant and positive influence on local revenue in the tourism sub-sector. Meanwhile, the number of tourist attractions has no effect on the local revenue of the tourism sub-sector.